2021
DOI: 10.1002/hed.26627
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for thyroidectomy technique: Comparing traditional and transoral approaches

Abstract: Background We investigated preferences between the transcervical and transoral thyroidectomy approach in the United States and Israel. Methods An online survey assessing scar attitudes and surgical preferences, in English and Hebrew, was distributed on http://thyca.com and other platforms. Results 928 and 339 responses from the United States and Israel cohorts, respectively, were analyzed. In both countries, individuals without prior thyroidectomy preferred a scarless approach when hypothetical risks equaled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…The importance of patient preference is further supported by the work of Choi et al which show that TCA scars result in an HRQOL deficit regardless of scar type, and the work of Chen et al showing patient preference for scarless approaches when risks are equivalent between approaches. 6,45 In this investigation, patients self-selected their surgical approach, hence individuals that were particularly skin-conscious and motivated to avoid cervical incisions presumably underwent TOETVA thyroidectomy. 40 While likely unfeasible, in a hypothetical investigation in which patients were randomized into surgical approaches, the TCA group may have worse HRQOL due to the discontent of skin-conscious individuals randomized into the approach.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient preference is further supported by the work of Choi et al which show that TCA scars result in an HRQOL deficit regardless of scar type, and the work of Chen et al showing patient preference for scarless approaches when risks are equivalent between approaches. 6,45 In this investigation, patients self-selected their surgical approach, hence individuals that were particularly skin-conscious and motivated to avoid cervical incisions presumably underwent TOETVA thyroidectomy. 40 While likely unfeasible, in a hypothetical investigation in which patients were randomized into surgical approaches, the TCA group may have worse HRQOL due to the discontent of skin-conscious individuals randomized into the approach.…”
Section: Discussionmentioning
confidence: 99%
“…Sawka et al 26–28 found that thyroid cancer patients were most concerned about treatment side effects. A report comparing traditional and transoral approaches highlighted patient interest in scarless thyroidectomy 29 . Taken together, there was a paucity of literature on the concerns and topics of interest to patients undergoing thyroid surgery such as thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…While some reported scar to be the most commonly reported adverse event, 49 with an adverse effect on the QoL, 50 others reported no impact on QoL 51,52 . This was further verified by significant differences in results reported on patients’ willingness to undergo scarless procedures 53,54 . Women, younger patients, patients with a tendency to heal with hypertrophic scars or keloid and patients with benign thyroid pathology have all been reported to be more concerned with a neck scar and to favour remote access thyroidectomy 54,55 .…”
Section: Possible Clinical Concerns Regarding Surgical Management Of Gdmentioning
confidence: 94%
“…51,52 This was further verified by significant differences in results reported on patients' willingness to undergo scarless procedures. 53,54 Women, younger patients, patients with a tendency to heal with hypertrophic scars or keloid and patients with benign thyroid pathology have all been reported to be more concerned with a neck scar and to favour remote access thyroidectomy. 54,55 Feasibility and safety of transoral thyroidectomy approach among the paediatric population was recently shown, 56 allowing for future investigations on the safety of transoral approach among paediatric GD patients.…”
Section: Neck Scarmentioning
confidence: 99%